Difficulties in literacy: the contributions of psych pedagogical assessment to the school intervention plan (Research, Society and Development, 2021)
This research was supported by the assumption that the psychopedagogical evaluation of a subject who has some difficulties in the literacy process can contribute to the elaboration of a pedagogical proposal that promotes the success of their learning. In the meantime, the objective was to make use of psychopedagogical assessment as an instrument to identify the difficulties related to the acquisition of reading and writing skills, in order to identify possible ways of pedagogical intervention. From a qualitative point of view, with the adoption of procedures and surveys of socio-environmental issues, document analysis, application of protocols, analysis of the data found and recommendations, the theoretical basis was anchored in the postulates of Social Sciences, in compliance with the ideas of researchers in the field of education (Jardini, 2010; Illich, 2002; Ferreiro e Teberosky, 1985) and neuro-learning studies (Capellini, Smythe, & Silva, 2012; Capovilla & Seabra, 2012a, 2012b, 2013; Seabra, Trevisan, & Capovilla, 2012; Sánches 2004). It was concluded that the results obtained through psychopedagogical evaluation point to ways for the elaboration of pedagogical activities that can contribute to the child's learning.